Lighthouse Schools and Crop Museums in the Philippines - Anunciado, M.S; Rio, S.D; Umali, D.J; Tamondong, S; Monville-Oro, Emilita; Gonsalves, Julian Francis; Hunter, Danny; Borelli, Teresa; Mendonce, Sharon (2023)
In The Philippines, Lighthouse Schools (LSs) and school-based Crop Museums (CMs) serve as repositories of crop biodiversity. Specifically, LSs are research sites where the integration of school feeding, nutrition education and school gardens, is demonstrated and evidence is established; while CMs are located within the large network of LS and act as seed banks that enable the multiplication and exchange of crop types and varieties across schools. Together they have helped conserve and promote multiple varieties of traditional and indigenous vegetables (IVs)and fruits.